Identifying the factors affecting the production of juice and wine from the autochthonous Bayanshira grape variety - Fataliyev, Hasil; Aghazade, Yahya; Heydarov, Elnur; Gadimova, Natavan; Ismayilov, Mehman; Imanova, Konul (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is juice and wine samples obtained from the Bayanshira grape variety. A number of studies were conducted on the Bayanshira grape variety, but the dynamics of berry ripening and the mechanical composition of the bunch, the effect of applied technological methods on the juice and wine indices have not been sufficiently studied. The study of the dynamics of berry ripening that the ripening index increased by the time of ripening and fluctuated within 27.46–43.92 The average length of a bunch is 21.93 cm, width is 9.70 cm, mass 172.11 g, the average number of berries in a bunch is 61.46 pieces, the weight of the comb in a bunch is 6.54 g. The average length of the berry was 18.46 mm, and the width was 18.40 mm, the average mass of the berry was 3.67 g. During the processing and storage of grape juice processed by the white method in different ways, it was found that the physicochemical composition of hot pasteurized samples was more susceptible to changes, compared to the control, and the samples treated with ultraviolet rays practically did not change their natural color and composition. The flow of nitrogenous substances into wine increased during their in yeast sediment from 30 to 90 days. An increase in temperature from 8–11 °C to 25–30 °C significantly increased the flow of nitrogenous substances from yeast sediment into wine compared to other options. These studies are important for production in terms of determining the dynamics of grape ripening at different stages of growth, the transformations that occur in the physicochemical composition during the storage of juice processed by different methods, and the regulation of the processes occurring during the stages of wine preparation. The results obtained can be used in family farms and wineries